Nivel de atención en parto humanizado en pacientes adolescentes de 14-18 años atendidas en el Hospital Básico Playas en el periodo mayo a septiembre del 2019 - Briones Mendoza, Kelvin Patricio (2019)
This research determines the level of care in humanized childbirth in adolescent patients performed at the Playas Basic Hospital, for which we consulted different sources of information both bibliographic and data obtained at the place where the research was conducted, the type of applied research corresponds to the exploratory, prospective and transversal study, since it was carried out in a period of four months, the technique to collect data was through surveys aimed at patients and health personnel who maintained contact with pregnant women in labor, delivery and postpartum. In this way, and based on the results obtained, the main conclusion is established: The care and good treatment of health professionals including nursing received towards adolescents who obtained their delivery at the Playas Basic Hospital with a population of 64 postpartum women was established , 48% indicate that it is excellent that they are equivalent to 31 adolescents, followed by 42% that indicate that the treatment received with a total of 27 adolescents was good, 6% on the contrary, tells us that it was bad with a total of 2 teenagers, and 3% regular. The study that was carried out in the basic hospital of beaches shows that the highest percentage of adolescents who had their humanized delivery corresponds to the age of 18 years followed by the adolescents of 15 years, this generates greater risk during the assessment and labor and affects the emotional state.